Environmentally Caring Character Education Strategy at MIN 1 Malang City - Neng Yuyun Yuningsih; Faridi Faridi; Dina Mardiana (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
The environment is an important element of human life, not only as a place to live but also plays a role as a supporter of various activities carried out. As stated by Gustavo in one of his writings, the environment is the sum total of all conditions that affect the existence, growth and well-being of an organism on earth. Every life is part of the environment, including the air we breathe, the condition of the body and the goods we consume. This study aims to describe the implementation of environmental character education strategies at MIN 1 Malang City and describe the supporting and inhibiting factors of environmental character education strategies at MIN 1 Malang City. As an educational institution committed to environmental issues, MIN 1 Malang City has developed various programs and activities designed to shape school citizens who have awareness, concern and real action in protecting the environment. This study uses a qualitative approach with a case study method, data collected through observation, interviews, documentation and triangulation techniques. The results of this study can be concluded that MIN 1 Malang City has successfully implemented various effective strategies in instilling environmental character education in school citizens, the programs implemented have had a positive impact on increasing students' awareness, concern and real action in protecting the environment. Even though there were several challenges faced, MIN 1 Malang City was able to overcome them well.